Plasma Biomarkers for Neuronal Ceroid Lipofuscinosis - Hersrud, Samantha L. (FEBS J, 2015)
The neuronal ceroid lipofuscinoses (NCLs) are a group of neurodegenerative genetic diseases that primarily affect children and have no known cure. A unified clinical rating scale for the juvenile form of NCL (JNCL) has been developed, but it has not been validated in other subtypes and does not give a true measure of the pathophysiological changes that may be occurring during disease progression. In this study, we have identified candidate biomarkers in blood plasma of NCL disease using multiple proteomic approaches, with the aim of developing a panel of biomarkers that could serve as a metric for therapeutic response. Candidate biomarkers were identified as proteins with levels that significantly differed between patients and controls in both sample sets. The seven candidates identified have previously been associated with neurodegenerative and inflammatory diseases. Multiplex immunoassay based testing was the most efficient and effective evaluation technique and could be employed on a broad scale to track patient response to treatment.